High-fat diet-induced obesity exacerbates kainic acid-induced hippocampal cell death. Issue 1 (December 2015) - Kang, Dong; Heo, Rok; Yi, Chin-ok; Kim, Hwajin; Choi, Chang; Roh, Gu
Abstract Background Obesity has deleterious effects on the brain, and metabolic dysfunction may exacerbate the outcomes of seizures and brain injuries. However, it is unclear whether obesity affects excitotoxicity-induced neuronal cell death. The purpose of this study was to investigate the effects of a high-fat diet (HFD) on neuroinflammation and oxidative stress in the hippocampus of kainic acid (KA)-treated mice. Results Mice were fed with a HFD or normal diet for 8 weeks and then received a systemic injection of KA. HFD-fed mice showed hypercholesterolemia, insulin resistance, and hepatic steatosis. HFD-fed mice showed greater susceptibility to KA-induced seizures, an increased number of terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL)-positive cells, neuroinflammation, and oxidative stress. Furthermore, we found that KA treatment increased HFD-induced calpain1, nuclear factor E2-related factor 2, and heme oxygenase-1 expression in the hippocampus. Conclusions These findings imply that complex mechanisms affected by obesity-induced systemic inflammation, neuroinflammation, ER stress, calcium overload, and oxidative stress may contribute to neuronal death after brain injury.